2008
DOI: 10.1111/j.1600-0714.2008.00716.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestations of HIV infection in adult patients from the province of Sancti Spiritus, Cuba

Abstract: This study described the prevalence of HIV-OL in 154 HIV-infected patients which represent about 80% of those known to be infected in the province of Sancti Spiritus. The prevalence of HIV-OL was lower than those reported from developing countries. Oral hairy leucoplakia and oral candidiasis were the most prevalent HIV-OL. Smoking and CD4(+) cells count <500 cells/mm(3) were the two factors independently associated with the presence of HIV-OL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
0
14
0
3
Order By: Relevance
“…Furthermore, smoking among people living with HIV increases susceptibility to infections such as bacterial pneumonia, oral candidiasis, and tuberculosis 9, 10, 11. A case-control study 12 among 279 ART-naive HIV-positive men in South Africa found that current smoking tripled the risk of pulmonary tuberculosis (adjusted odds ratio [OR] 3·2; 95% CI 1·3–7·9, p=0·01).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, smoking among people living with HIV increases susceptibility to infections such as bacterial pneumonia, oral candidiasis, and tuberculosis 9, 10, 11. A case-control study 12 among 279 ART-naive HIV-positive men in South Africa found that current smoking tripled the risk of pulmonary tuberculosis (adjusted odds ratio [OR] 3·2; 95% CI 1·3–7·9, p=0·01).…”
Section: Introductionmentioning
confidence: 99%
“…Les affections buccales peuvent être présentes chez plus de 50 % des personnes avec l'infection VIH et plus de 80 % chez les personnes à la phase SIDA [8]. Leur incidence a substantiellement diminué à l'ère des traitements antirétro-viraux [9,10]. Les manifestations buccales constituent souvent les premières manifestations cliniques de l'infection à VIH ou de son évolution [2,5,6,8], d'où leur valeur diagnostique et pronostique [6].…”
Section: Introductionunclassified
“…4 An evaluation of 237 HIV-positive patients revealed high prevalence of oral lesions, with candidiasis, oral hairy leukoplakia, and HIV-related periodontal disease being three most common manifestations, and candidiasis significantly associated with low CD4 count (less than 200). 9 Other studies have also shown an association between low CD4 counts and candidiasis, linear gingival erythema, angular cheilitis, scabies, paronychia, oral pigmentation, diffuse hair loss and other oral symptoms. 11,12 …”
Section: Introductionmentioning
confidence: 93%
“…8 Early diagnosis and appropriate treatment of oral lesions have great influence on patients’ general health and can reduce the mortality rate of the disease. 9 Although some lesions such as candidiasis and hairy leukoplakia are considered as prognostic factor, recent data have indicated that concurrent existence of multiple and variable oral lesions is accompanied with poor prognosis of the disease. 10 Reduction of circulating CD4 count is the main criteria for assessing the immunosuppression status in HIV-positive patients.…”
Section: Introductionmentioning
confidence: 99%